A View on Teaching Philosophy in Curriculum Implementation at the Indonesia University of Education - Wahyudin, Dinn (SOSIOHUMANIKA, 2016)
ABSTRACT: Efforts have been done by TEIs (Teacher Education Institutions) in Indonesia. UPI (Indonesia University of Education) in Bandung is having effort to reformulate its curriculum. The formula of redesign of professional education for teachers that was developed by UPI is a response to need for better teacher education. This study focused on philosophy of education in the implementation of curriculum in Study Program at UPI. In curriculum implementation, aspect of philosophy of teaching is very important in the educational institutions. It is applied in the teaching-learning situations, in the conduct of research, and in developing educational policies. Teaching philosophy of individual lecturer is based on the university and facultyâs vision and mission, concept, beliefs, and attitudes on teaching, and how they put these into the teaching-learning process. This has implications to classroom management, pedagogy, facilitating and evaluating learning, and curriculum development. This study presents some empirical base data from two faculties in UPI, namely FIP (Faculty of Educational Sciences) and FPTK (Faculty of Technology and Vocational Education). Instruments used were questioners, interview, focused group discussion, and documentation study. Result shows that the implementation of curriculum and individual teaching philosophies of lecturers are strongly influenced and inspired by institutional teaching philosophy and its vision and mission. KEY WORD: Curriculum Development; Teaching Philosophy; Teacher Education; Indonesia University of Education; Implementation of Curriculum.Â RESUME: âPandangan tentang Falsafah Pembelajaran dalam Implementasi Kurikulum di Universitas Pendidikan Indonesiaâ. Pembenahan LPTK (Lembaga Pendidikan Tenaga Kependidikan) di Indonesia terus dilakukan. UPI (Universitas Pendidikan Indonesia), sebagai salah satu LPTK di Indonesia, tengah melakukan reformulasi pendidikan profesional guru,Â sebagai respon terhadap tuntutan kebutuhan guru yang lebih bermutu dan bermartabat. Studi ini memfokuskan pada kajian falsafah pembelajaran dalamÂ  implementasi kurikulumÂ  di UPI. Studi ini menggunakan pendekatan penelitian kualitatif dan kuantitatif, dengan sampel melibatkan unsur pimpinanÂ  fakultas dan program studi. Dalam implementasi kurikulum, telaah filsafat pembelajaran menjadi isu penting dalam praktek di fakultas atau jurusan. Hal tersebut diimplementasikan dalam situasi belajar-mengajar, penelitian, ataupun dalam mengembangkan kebijakan pendidikan. Penelitian ini menyajikan beberapa data dasar empiris dari dua Fakultas di UPI, yaitu FIP (Fakultas Ilmu Pendidikan) dan FPTK (Fakultas Pendidikan Teknologi dan Kejuruan), yaituÂ  bagaimana falsafah pembelajaran yang dianut setiap individu dosen dipengaruhi pula oleh sistem nilai, visi dan misiÂ  universitas, fakultas, dan program studi. Instrumen yang digunakan adalah kuesioner, wawancara, FGD (Focused Group Discussion), dan studi dokumentasi. Hasil penelitian menunjukan bahwa dalam implementasi kurikulum dan filosofi mengajar individu dosen sangat dipengaruhi dan terinspirasi oleh filosofi, sistem nilai, serta visi dan misi lembaga penaungnya.KATA KUNCI: Pengembangan Kurikulum; Falsafah Pendidikan; Pendidikan Guru, Universitas Pendidikan Indonesia; Implementasi Kurikulum.About the Author: Dr. Dinn Wahyudin is a Senior Lecturer at the Faculty of Educational Sciences UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. For academic interests, the author is able to be contacted via his e-mail at: dinn_wahyudin@upi.edu How to cite this article? Wahyudin, Dinn. (2016). âA View on Teaching Philosophy in Curriculum Implementation at the Indonesia University of Educationâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.9(2) November, pp.235-248. Bandung, Indonesia: Minda Masagi Press and UPI Bandung, ISSN 1979-0112. Chronicle of the article: Accepted (September 29, 2016); Revised (October 28, 2016); and Published (November 30, 2016).